Improved CAVLC for H.264/AVC Lossless Intra-Coding - HEO, Jin; KIM, Seung-Hwan; HO, Yo-Sung (IEEE transactions on circuits and systems for video technology, 2010)
Context-based adaptive variable length coding (CAVLC) for the H.264/advanced video coding (AVC) standard was originally designed for lossy video coding, and as such does not yield adequate performance for lossless video coding. In this paper, we propose an improved CAVLC for lossless intra-coding by considering the statistical differences in residual data between lossy and lossless coding. From experimental results, we confirm that the proposed method provides approximately 9% bit saving in terms of a compression ratio compared with the current H.264/AVC fidelity range extensions high profile.